2013
DOI: 10.3171/2013.4.focus13103
|View full text |Cite
|
Sign up to set email alerts
|

Ventral fusion versus dorsal fusion: determining the optimal treatment for cervical spondylotic myelopathy

Abstract: Cervical spondylotic myelopathy (CSM) often can be surgically treated by either ventral or dorsal decompression and fusion. However, there is a lack of high-level evidence on the relative advantages and disadvantages for these treatments of CSM. The authors' goal was to provide a comprehensive review of the relative benefits of ventral versus dorsal fusion in terms of quality of life (QOL) outcomes, complications, and costs. They reviewed 7 studies on CSM published between 2003 and 2013 and summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…Far fewer studies have been published on PCF outcomes than on ACF outcomes (especially anterior cervical discectomy and fusion outcomes), most likely because far fewer PCFs than ACFs are performed [1,4−6]. Posterior cervical fusion patient-reported outcomes, as well as complication and reoperation rates, have been assembled mostly in review articles from studies that compared PCF (laminectomy and fusion) with laminoplasty [7−12] or PCF with ACF [13]. A systematic review, published in 2009, of 11 studies on cervical laminectomy and fusion reported on patients' improvement in neurologic function and in Japanese Orthopaedic Association (JOA) score [14].…”
Section: Introductionmentioning
confidence: 99%
“…Far fewer studies have been published on PCF outcomes than on ACF outcomes (especially anterior cervical discectomy and fusion outcomes), most likely because far fewer PCFs than ACFs are performed [1,4−6]. Posterior cervical fusion patient-reported outcomes, as well as complication and reoperation rates, have been assembled mostly in review articles from studies that compared PCF (laminectomy and fusion) with laminoplasty [7−12] or PCF with ACF [13]. A systematic review, published in 2009, of 11 studies on cervical laminectomy and fusion reported on patients' improvement in neurologic function and in Japanese Orthopaedic Association (JOA) score [14].…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, a recent review by Alvin et al found that many cost studies in the ACF-PCF comparison literature fail to adequately include indirect costs in their analyses. [2] Despite this limitation, Alvin et al conclude that both dorsal and ventral decompression and fusion, when used to treat CSM, can lead to significant improvements in quality of life (QOL). Still, uncertainty remains about which of the two approaches is preferred in the treatment of CSM.…”
Section: Discussionmentioning
confidence: 99%
“…Although complications such as dysphagia and dysphonia are more common in ACF, the procedure enables direct decompression of cervical pathologies in kyphotic, neutral, or lordotic alignment. While PCF can be used in patients with neutral or lordotic spinal alignment, [2] it can lead to significant postoperative muscle pain. [36] …”
Section: Introductionmentioning
confidence: 99%
“…Bu cerrahi hedefler servikal omurgaya çeşitli cerrahi yaklaşım yolları kullanılarak sağlanabilir 3,4 . SSMR cerrahisi sonrası geç dönem nörolojik tabloda bozulmanın en önemli sebepleri instabilite, servikal dizilimde bozulma ve komşu segment hastalığıdır.İnstabilite ve servikal dizilimde bozulma posterior cerrahi yaklaşımları takiben daha sık karşımıza çıkan bir problemdir.Komşu segment hastalığı ise literatürde aksini bildiren yayınlar olmakla birlikte anterior cerrahi yaklaşımları takiben daha sık karşılaşıldığı söylenebilir [3][4][5][6][7][8][9] .…”
Section: Introductionunclassified